Relationship of Parity, Maternal Age and Birth Weight with the Duration of the Second Stage of Labor - Ismawati Hanis; Chairuna Chairuna; Sri Handayani (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: second stage of labor begins when the cervix is fully dilated and ends with the birth of a baby. The duration of second stage of labor commonly lasts 2 hours for primigravida mothers and one hour for multigravida mothers. Prolonged labor is one of complications experienced by mothers in second stage of labor. Prolonged labor can cause several complications for both mothers and infants. Prolonged labor can harm both the mother and the infant. The harmful effects of complications during second stage of labor for mothers include the incidence of uterine atony, laceration, bleeding, infection, fatigue and shock and improving the birth rate with the C-section incision. Whereas the harmful effects of complications during second stage of labor for infants include asphyxiated, cerebral trauma caused by pressure on the head of the fetus, the injury due to action, and premature rupture of membranes. The severity of the injury increases continuously along with the longer of the duration of the labor process, and the risk of which rises quickly after 24 hours. The longer the labor, the higher the morbidity as well as the mortality. The stage of labor affected by all such factors mentioned is called the second stage of laborObjective: to find out the relationship of parity, maternal age, and birth weight with the duration of the second stage of labor.Methods: this study applied a quantitative research design using an analytical survey method through a cross sectional approach. The sample in this study was chosen using total sampling method with the purposive sampling technique, namely, that the sample was all maternity mothers who were coincidentally present at the time of the study at UPTD Karya Mukti Public Health Center in August 2021. Then, Chi-square statistical test was used to determine the relationship between independent variables and dependent variable.Results: of the 30 respondents, 20 respondents whose parity was not at risk (95.2%) experienced normal duration of second stage of labor, while 5 respondents (55.6%) whose parity was at risk experienced normal duration of second stage of labor. 21 respondents whose maternal age was not at risk (95.5%) experienced normal duration of second stage of labor, while 4 respondents whose maternal age was at risk (50%) experienced normal duration second stage of labor. 23 respondents (92%) with normal birth weight babies experienced normal duration of second stage of labor, while 2 respondents (40%)with large birth weight babies experienced normal duration of second stage of labor. The results of the Chi-square statistical test showed that there was a significant relationship between parity and the duration of the second stage of labor with the p-value of 0.019 £ 0.05 and the OR value of 9.157. There was a significant relationship between maternal age and the duration of the second stage of labor with the p-value of 0.011 £ 0.05 and the OR value of 5.387, and there was a significant relationship between birth weight and the duration of the second stage of labor with the p-value of 0.022 £ 0.05 and OR value of 3.405.Conclusions: there was a relationship between parity and the duration of second stage of labor. There was a relationship between maternal age and the duration of second stage of labor, and there was a relationship between birth weight and the duration of second stage of labor. Suggestions: It is hoped that health workers will further improve IEC (Information, Education, and Communication) regarding safe gestational age, safe parity and balanced nutrition as a form of antenatal care for pregnant women which is very influential, especially during the second stage of labor. In addition, for pregnant women, it is better to perform quality ANC to predict whether mothers will be likely to experience prolonged labor or not and also to prevent prolonged labor and other complications of pregnancy and labor. Then, based on the results of ANC tests, the mothers immediately referred to a more adequate hospitals/maternity hospitals to monitor the condition of their pregnancy so as to prevent the risk that will be faced by the mothers and fetus during labor. Keywords: Parity, Maternal Age, Birth Weight, Duration of Second Stage Labor